2009
DOI: 10.1063/1.3083548
|View full text |Cite
|
Sign up to set email alerts
|

Realistic adsorption geometries and binding affinities of metal nanoparticles onto the surface of carbon nanotubes

Abstract: Articles you may be interested inInsight into the description of van der Waals forces for benzene adsorption on transition metal (111) Adsorption of transition-metal atoms on boron nitride nanotube: A density-functional study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
5
20
0
2
Order By: Relevance
“…These behaviors are linked to the nature of the interaction between metals and CNTs but not only: nucleation rate and wetting properties must be also considered. [49]. Consequently our experimental results are in agreement with these calculations.…”
Section: Theoretical Metal Deposition In At%supporting
confidence: 94%
See 1 more Smart Citation
“…These behaviors are linked to the nature of the interaction between metals and CNTs but not only: nucleation rate and wetting properties must be also considered. [49]. Consequently our experimental results are in agreement with these calculations.…”
Section: Theoretical Metal Deposition In At%supporting
confidence: 94%
“…Only few characterizations of this CNTs-metal interface have been reported from chemical and crystallographic point of views [43][44][45]. Some calculations have been realized and allow explaining the experimental data [46][47][48][49][50]. One can however wonder if the CNTs-metal interface depends on the functionalization method and/or deposition process.…”
Section: Introductionmentioning
confidence: 94%
“…Adsorption geometries and binding affinities of metal nanoparticles onto CNTs have been investigated through DFT calculations [572]. Clusters of 13 metal atoms were used as models for metal nanoparticles.…”
Section: Platinum Clustersmentioning
confidence: 99%
“…The contacting force between SWCNTs and Al is this kind. In addition, the strong oxidation in air will weaken the binding affinity of Al with SWCNTs further [11]. The other is the chemisorption caused by covalent bonds which is much stronger than the former.…”
Section: Theory and Considerationmentioning
confidence: 99%
“…The other is the chemisorption caused by covalent bonds which is much stronger than the former. For SWCNTs, it is generated by sp2→sp3 transition of metal and adjacent C-atoms, such as SWCNTs-Pt and SWCNTs-Ti [11]. It has been reported that interaction energies of transition metals enhance with the number of vacancies in d orbital.…”
Section: Theory and Considerationmentioning
confidence: 99%